2015
DOI: 10.1039/c5ra00798d
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Rhodamine B over Ag modified ferroelectric BaTiO3 under simulated solar light: pathways and mechanism

Abstract: Reaction mechanism for RhB degradation over a self-polarised semiconductor, BaTiO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 59 publications
6
37
0
Order By: Relevance
“…The new peaks in the spectrum are associated with the intermediate products formed during degradation. The NMR results further confirmed that the de-ethylation and degradative changes of RhB occurs during the photo degradation processes 32,33 .…”
Section: Resultssupporting
confidence: 64%
“…The new peaks in the spectrum are associated with the intermediate products formed during degradation. The NMR results further confirmed that the de-ethylation and degradative changes of RhB occurs during the photo degradation processes 32,33 .…”
Section: Resultssupporting
confidence: 64%
“…Recent studies comparing the photocatalytic reactivity of BaTiO 3 have shown that tetragonal, ferroelectric BaTiO 3 nanoparticles exhibit signifi cantly higher activities than those observed when the dominant crystal phase is the non-ferroelectric cubic phase. [ 9,22 ] Herein we report an investigation, using TAS, of charge carrier dynamics in a prototypical ferroelectric material: BaTiO 3 . The potential to modulate spontaneous polarization within BaTiO 3 through selection of both crystal structure [ 23 ] and temperature [ 24 ] makes this material an ideal model system to study the impact of the internal fi elds upon charge carrier dynamics.…”
Section: Doi: 101002/adma201601238mentioning
confidence: 99%
“…Although the formed intermediates were not characterized in this work, there is a vast literature exploring different reaction of intermediates from Rhodamine B [40][41][42]. As an example, in recent publication, Cui et al demonstrated that benzoic acid was the major identifiable breakdown intermediate during the photodegradation of Rhodamine B over Ag modified ferroelectric BaTiO 3 under simulated solar light [43].…”
Section: Reusability Of Ce-tio 2 /Diatomite Compositementioning
confidence: 99%